Duplication and Replacement as Means of Connecting the Prescriptions - Sargsyan, Artashes (Bulletin of Yerevan University B: Philology, 2024)
The study of the connection of sentences in a paragraph is one of the important problems of text linguistics. Just as there are ways to connect words and components of complex sentences, there are ways to connect sentences in a paragraph. There are quite a few of them, but repetition and replacement play the most important role. They have their own forms of manifestation, which are examined in the article. Repetition can be verbal and grammatical. The replacement is made with a pronoun, nominalization, synonym, description. By these means, connections are created between the sentences in the paragraph, which in some cases are stronger, in others, relatively weak. If intertextual connections are not created between sentences, then there will be a set of sentences, but not a text, although each sentence will express its meaning. The stylistic factor is also important in the choice of means of intertextual connection.